Maintenance management for surface water drainage / Mohd Nor Hafizie Hasbullah - Hasbullah, Mohd Nor Hafizie (Faculty of Architecture, Planning and Surveying, 2010)
Maintenance management of drainage is one field where there will be an organization or body in maintenance management. Especially in drainage maintenance which required work commitment that high pursuant to work maintains from managerial level until to degree maintenance which is done by those people are informed in managing this drainage. This would be vital to keep drainage system condition so that are constantly in good condition and fulfill their function. Apart from that, to ensure comfort and peaceful coexistence of population at the area because if system drainage in an area that bad, this would be administering problem to locals especially flood problem and others problem more that related about drainage. In now found system drainage already less effective to transmit water out quickly than those should. Realizing importance this, five party fruit the respective has been chosen for study namely four from Local Authorities namely Majlis Bandar Raya Petaling Jaya (MBPJ), Majlis Bandar Raya Shah A lam (MBSA), Majlis Perbandaran Subang Jaya (MPSJ), Majlis Perbandaran Klang (MPK) and one from higher learning centre namely University Teknologi Mara Shah A lam (UITM). Study this focused on drainage maintenance management and some of the problems that stemmed from drainage this. Analyzing also made to find out the causes to problems which related. Lastly, summary would be made based on objective and some suggestions would be addressed to overcome problem that be pursuant to maintenance management work drainage in areas and also suggestion to increase more system those managing be.